'Carbon' in forest carbon projects: Evidence from India. (9th August 2022) - Aggarwal, Ashish
ABSTRACT: This research assesses the carbon claims of two forest carbon projects in the states of Haryana and Himachal Pradesh in India, which are being supported by European Union and World Bank respectively. This research finds that both the projects had sequestered only 37% and 3% of the carbon estimated in the project documents up to their first verification period. Only one of the projects i.e., Himachal Pradesh project could earn 38% of the projected credits. Haryana project could not claim carbon credits as more than half of the participants had left the project due to various issues. Haryana and Himachal projects have reported high costs of USD 0.5 million and USD 1.83 million respectively. Both the projects have become unsustainable early in their lifecycle due to low or no carbon revenues, high costs and other governance issues. The available empirical evidence from across the globe also suggests high costs and mixed results on carbon from the forest carbon projects. Hence, it is imperative to revisit the established narrative of 'big and cheap carbon' with the robust empirical evidence before further scaling up of the forest carbon projects.